2011
DOI: 10.1186/1752-1947-5-347
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent locked knee caused by an impaction fracture following inferior patellar dislocation: a case report

Abstract: IntroductionLocked knee caused by inferior patellar dislocation is considered rare in elderly patients. It was originally thought that, in the osteoarthritic knee, osteophytes on the pole of the patella become entrapped in the inter-condylar notch, which is managed by performing closed reduction and immobilization in a knee splint for three to four weeks. We present an unusual case of a locked knee with an impaction fracture. To the best of our knowledge, there have been no previous reports of such impaction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There are conflicting reports of the recurrence of the inferior patella dislocation. The group which reported recurrence of the dislocation advocates surgical resection of the superior osteophyte [9]. In this case, the superior osteophyte was already fractured and it highlights the importance of its role in the mechanism of dislocation.…”
Section: Discussion/conclusionmentioning
confidence: 85%
See 1 more Smart Citation
“…There are conflicting reports of the recurrence of the inferior patella dislocation. The group which reported recurrence of the dislocation advocates surgical resection of the superior osteophyte [9]. In this case, the superior osteophyte was already fractured and it highlights the importance of its role in the mechanism of dislocation.…”
Section: Discussion/conclusionmentioning
confidence: 85%
“…In case of failure of closed reduction under simple analgesia, attempt under general anaesthesia is advocated [8]. Osteophyte impaction may hinder closed reduction and necessitates osteophyte resection arthroscopically or open reduction [4, 9]. There are conflicting reports of the recurrence of the inferior patella dislocation.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Most of these cases require an open reduction as a primary procedure (3,4,8,9,12,15,16), only the cases with incomplete patellar rotation can be treated conservatively (3,10,12,14). Distinctly, only three authors reported an osteochondral fracture of the lateral femoral condyle (2,6,18). Two of these authors treated the fracture during open surgery (6,18).…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen et al [ 9 ] and Syed and Ramesh [ 2 ], however, reported that dislocation recurred and stated that osteophyte resection was necessary to prevent recurrence. Barlow et al [ 10 ] also reported the occurrence of recurrent dislocation in a case of inferior dislocation of the patella in which an osteophyte on the superior pole of the patella had become impacted in the lateral condyle of the femur, with treatment by arthroscopic removal of the osteophyte and trimming of the articular surface of the lateral condyle. In Case 1, open osteosynthesis of the femoral condyle fracture was performed with the aim of early ambulation, during which the remaining osteophyte on the superior pole of the patella was resected and the floating osteophyte removed.…”
Section: Discussionmentioning
confidence: 99%